Carnivore conservation (Cambridge University Press, 2001)
This volume reviews and summarizes the current state of the field, describes limitations and opportunities for carnivore conservation, and offers a conceptual framework for future research and applied management. It will be of interest to students and researchers of conservation biology, mammalogy, animal behavior, ecology, and evolution.